2020
DOI: 10.1021/acsbiomaterials.0c00746
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Feature of Intermediate Water in Hydrated Poly(ω-methoxyalkyl acrylate)s by Molecular Dynamics Simulation and Differential Scanning Calorimetry Measurement

Abstract: Intermediate water (IW) has been reported to play an important role in nonthrombogenicity of biomaterials. However, clear insights into the IW in the hydrated polymer are still debated. In this study, a series of molecular dynamics simulations was performed to identify the IW structure in hydrated poly­(ω-methoxyalkyl acrylate)­s (PMCxAs, where x indicates the number of methylene carbons) with x = 1–6. Through the quantitative comparison with experimental measurements, IW molecules were suggested to mainly com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(55 citation statements)
references
References 46 publications
(97 reference statements)
3
52
0
Order By: Relevance
“…In a previous experimental study of poly­(ω-methoxyalkyl acrylate)­s (PMC x A, where x indicates the number of methylene carbons in-between ester and ether oxygens of the side-chain) (Figure ), the amounts of adhered platelet and adsorbed fibrinogen on the PMC x A surface have been found to roughly increase with the increase of the side-chain length from x = 2 to 6 because of the decrease in the IW content and increase in the hydrophobicity; however, the conformational change of the adsorbed fibrinogen was suppressed . We have applied MD simulations to investigate the IW structure in the hydrated PMC x A and found that the IW molecules mainly come from BW1 . In addition, the BW1 content of PMC x A was found to decrease with the increase of the side-chain length from x = 2 to 6 .…”
Section: Introductionsupporting
confidence: 51%
See 3 more Smart Citations
“…In a previous experimental study of poly­(ω-methoxyalkyl acrylate)­s (PMC x A, where x indicates the number of methylene carbons in-between ester and ether oxygens of the side-chain) (Figure ), the amounts of adhered platelet and adsorbed fibrinogen on the PMC x A surface have been found to roughly increase with the increase of the side-chain length from x = 2 to 6 because of the decrease in the IW content and increase in the hydrophobicity; however, the conformational change of the adsorbed fibrinogen was suppressed . We have applied MD simulations to investigate the IW structure in the hydrated PMC x A and found that the IW molecules mainly come from BW1 . In addition, the BW1 content of PMC x A was found to decrease with the increase of the side-chain length from x = 2 to 6 .…”
Section: Introductionsupporting
confidence: 51%
“…In this work, the bound water (BW) is defined as the water interacting with polymer oxygen through the hydrogen (H) bonding following our previous study. , The H bond is defined by referring to geometric criteria among all possible acceptors, donors, and hydrogen atoms. , We assume that the H bond is formed when the distance between an acceptor and a donor is smaller than 0.35 nm and the angle formed by the hydrogen, donor, and acceptor atoms is less than 30°.…”
Section: Simulation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The arguments here are consistent with recent studies on the anti-fouling mechanism of polymer surfaces. [49][50][51][52] In these studies, water at a polymer-water interface is classified into three categories: nonfreezing water, intermediate water, and free water. Nonfreezing water is tightly bound to a surface and noncrystallizable even at −100 • C. Intermediate water is loosely bound to a surface and crystallizes below 0 • C. Free water is scarcely bound to a surface and crystalizes at 0 • C. Among them, intermediate water is considered to play a key role in the anti-fouling mechanism of a polymer surface.…”
Section: Simulationmentioning
confidence: 99%